Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1152/ajpregu.1998.274.1.r52
|View full text |Cite
|
Sign up to set email alerts
|

CytochromeP-450-derived eicosanoids participate in the renal functional effects of ET-1 in the anesthetized rat

Abstract: We evaluated the contribution of cytochrome P-450 (CYP450)-dependent arachidonic acid (AA) metabolites and prostanoids to the renal hemodynamic and tubular effects of endothelin-1 (ET-1) in anesthetized rats. Either ET-1 (0.3, 1.0, and 3 pmol ⋅ kg−1 ⋅ min−1) or vehicle was infused intravenously during two to three 30-min clearance experimental periods. Only high-dose ET-1 increased mean arterial pressure: control, 75 ± 3 mmHg vs. experimental, 84 ± 4 mmHg. A dose-dependent diuretic-natriuretic response to ET-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
60
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 17 publications
1
60
2
Order By: Relevance
“…Recent studies have indicated that CYP metabolites of AA play an important role as second messengers in the regulation of the tubular and vascular effects of peptide hormones and growth factors (1,3,37,40). For example, ANG II and endothelin stimulate the renal formation of 20-HETE, which contributes to the renal vasoconstrictor and natriuretic actions of these hormones (11,12,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that CYP metabolites of AA play an important role as second messengers in the regulation of the tubular and vascular effects of peptide hormones and growth factors (1,3,37,40). For example, ANG II and endothelin stimulate the renal formation of 20-HETE, which contributes to the renal vasoconstrictor and natriuretic actions of these hormones (11,12,35).…”
Section: Discussionmentioning
confidence: 99%
“…The release of 20-HETE in renal and peripheral blood vessels is stimulated by ANG II (5), phenylephrine (20a), endothelin (37), and serotonin (3). There is considerable evidence that 20-HETE contributes to the vasoconstrictor responses to these hormones by modulating potassium channel activity and calcium influx (1).…”
mentioning
confidence: 99%
“…3,7,9 Actions of ET-1, via ET A and ET B receptors, include phospholipase A 2 stimulation and the resultant increase in arachidonic acid-derived mediators. 1,7,15,21 Previous studies have investigated the involvement of CYP450 hydroxylase and COX metabolites in the renal vasoconstrictor response to ET-1. 7,9,10,16, 22 Oyekan et al, using in vitro and in vivo techniques, have shown that the CYP450 hydroxylase pathway contributes to the ET-1-evoked decrease in renal blood flow, but the role of the COX pathway appears to be complex.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,10,16, 22 Oyekan et al, using in vitro and in vivo techniques, have shown that the CYP450 hydroxylase pathway contributes to the ET-1-evoked decrease in renal blood flow, but the role of the COX pathway appears to be complex. 7,16,23 In the isolated perfused kidney, COX inhibition attenuated the renal vasoconstrictor response to ET-1, 16 but when studied in vivo, the COX inhibitor indomethacin potentiated the decrease in glomerular filtration rate elicited by ET-1. 7 These paradoxical findings demonstrating COX metabolites as positive and negative contributors to the ET-1-mediated vasoconstriction are not limited to the renal vasculature and may reflect experimental conditions or species variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation